2014
DOI: 10.1037/hea0000042
|View full text |Cite
|
Sign up to set email alerts
|

Spousal neuroticism moderates everyday problem-wellbeing associations in older couples.

Abstract: Findings are discussed in the context of evolutionary psychology and suggest that spousal neuroticism may serve adaptive functions by increasing vigilance and preparing older spouses to deal with everyday problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
3
13
0
1
Order By: Relevance
“…From this perspective, dispositional negativity represents a diathesis that promotes heightened levels of negative affect, pessimism, and avoidance motivation in the face of trait-relevant challenges (Eysenck, 1967;Gray & McNaughton, 2000;Kagan, Reznick, & Snidman, 1988;Spielberger, 1966;Zuckerman, 1976). The present results and other data (e.g., Aldinger et al, 2014;Shackman/Lemay, Dispositional negativity in the wild 24 Ching et al, 2014;David et al, 1997;Emmons & Diener, 1986;Howell, Ksendzova, Netingen, Yerahian, & Iyer, in press;Howell & Rodzon, 2011;Jacobs et al, 2011;Komulainen et al, 2014;Kuppens et al, 2007;Lay & Hoppmann, 2014;Leger et al, 2016;Snippe et al, in press;Soto & John, in press;Tennen et al, 2006;Watson, 1988;Watson & Clark, 1984;R. E. Wilson et al, in press;Zautra et al, 2005) underscore the need to broaden this perspective to encompass positive affect and positive experiences.…”
Section: Discussionsupporting
confidence: 73%
“…From this perspective, dispositional negativity represents a diathesis that promotes heightened levels of negative affect, pessimism, and avoidance motivation in the face of trait-relevant challenges (Eysenck, 1967;Gray & McNaughton, 2000;Kagan, Reznick, & Snidman, 1988;Spielberger, 1966;Zuckerman, 1976). The present results and other data (e.g., Aldinger et al, 2014;Shackman/Lemay, Dispositional negativity in the wild 24 Ching et al, 2014;David et al, 1997;Emmons & Diener, 1986;Howell, Ksendzova, Netingen, Yerahian, & Iyer, in press;Howell & Rodzon, 2011;Jacobs et al, 2011;Komulainen et al, 2014;Kuppens et al, 2007;Lay & Hoppmann, 2014;Leger et al, 2016;Snippe et al, in press;Soto & John, in press;Tennen et al, 2006;Watson, 1988;Watson & Clark, 1984;R. E. Wilson et al, in press;Zautra et al, 2005) underscore the need to broaden this perspective to encompass positive affect and positive experiences.…”
Section: Discussionsupporting
confidence: 73%
“…Most studies show a negative association between neuroticism and mental health [ 8 , 57 ], so one would also expect a moderating effect neuroticism on pain-to-mental health associations. In fact, there is previous evidence to suggest that the relationship between a stressor (i.e., everyday problems) and both affective and physical problems are moderated by spouse neuroticism [ 19 ]. While the present study replicated this moderating effect of spouse neuroticism on physical health status, this was not the case for mental well-being.…”
Section: Discussionmentioning
confidence: 99%
“…There is, indeed, some support for this contextual (i.e., moderating) role of spouse personality in the context of couples. For instance, a study showed that spouse neuroticism influenced the associations between everyday problems and affect and physical symptoms in older couples [ 19 ]. In another investigation, the relationship between patient personality and patient psychological health differed as a function of spouse personality [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 (See also Brewer et al, 2007; Carstensen, Pasupathi, Mayr, & Nesselroade, 2000; Ching et al, 2014; Eddington, Majestic, & Silvia, 2012; Emmons & Diener, 1986; Heiy & Cheavens, 2014; Hepburn & Eysenck, 1989; Kardum, 1999; Komulainen et al, 2014; Kuppens, Oravecz, & Tuerlinckx, 2010; Kuppens, Van Mechelen, Nezlek, Dossche, & Timmermans, 2007; Lay & Hoppmann, 2014; McConville & Cooper, 1999; Ode, Hilmert, Zielke, & Robinson, 2010; Ong, Zautra, & Reid, 2010; Park, Armeli, & Tennen, 2004; Rusting & Larsen, 1998; Schimmack, 2003; Sherry & Hall, 2009; Skalina, Gunthert, Ahrens, & Wenze, 2015; Tennen, Affleck, & Zautra, 2006; Tong et al, 2006; Verduyn & Brans, 2012; Watson, 1988; Williams, 1981, 1990; R. E. Wilson, Thompson, & Vazire, in press ).…”
mentioning
confidence: 99%